Speed of sound in methane under conditions of planetary interiors - White, Thomas G.; Poole, Hannah; McBride, Emma E.; Oliver, Matthew; Descamps, Adrien; Fletcher, Luke B.; Angermeier, W. Alex; Allen, Cameron H.; Appel, Karen; Condamine, Florian P.; Curry, Chandra B.; Dallari, Francesco; et al. (Physical Review Research, 2024)
We present direct observations of acoustic waves in warm dense matter. We analyze wave-number- and energy-resolved x-ray spectra taken from warm dense methane created by laser heating a cryogenic liquid jet. X-ray diffraction and inelastic free-electron scattering yield sample conditions of 0.3±0.1 eV and 0.8±0.1 g/cm-3, corresponding to a pressure of ∼13 GPa. Inelastic x-ray scattering was used to observe the collective oscillations of the ions. With a highly improved energy resolution of ∼50 meV, we could clearly distinguish the Brillouin peaks from the quasielastic Rayleigh feature. Data at different wave numbers were utilized to derive a sound speed of 5.9±0.5 km/s, marking a high-temperature data point for methane and demonstrating consistency with Birch's law in this parameter regime.
CRIS-Team Scopus Importer:2024-05-17